Karakteristik Inovasi Pendidikan, Strategi Pendidikan, dan Strategi Inovasi Pendidikan - Efendi, Ridwan; Ismail, Fajri; Afgani, Muhammad Win (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Educational innovation is a crucial factor in improving the quality of learning and adapting the education system to the demands of the modern era. The characteristics of educational innovation, educational strategies, and educational innovation strategies are closely interconnected in creating a more effective, adaptive, and relevant learning system. This study aims to analyze the concepts and relationships among these three aspects to understand how educational innovation strategies can be optimally implemented. This research employs a literature review method by examining various relevant sources, including books, scientific journals, and previous studies. The analysis focuses on the concept of educational innovation, the educational strategies applied in different learning systems, and innovation strategies that enhance the effectiveness of education. The findings indicate that educational innovation has key characteristics such as flexibility, sustainability, and adaptability to learning needs. Meanwhile, educational strategies serve as guidelines for designing a structured and well-directed learning process. Educational innovation strategies are necessary to systematically integrate innovations, including technology, learning methods, and curricula. This study emphasizes that the success of educational innovation depends on human resource readiness, policy support, and adequate infrastructure.